Datasets:

Modalities:
Text
Languages:
English
Libraries:
Datasets
License:
Zhangir Azerbayev
squashed?
4365a98
raw
history blame
11.6 kB
/-
Copyright (c) 2014 Floris van Doorn (c) 2016 Microsoft Corporation. All rights reserved.
Released under Apache 2.0 license as described in the file LICENSE.
Authors: Floris van Doorn, Leonardo de Moura, Jeremy Avigad, Mario Carneiro
-/
import algebra.group_power.order
/-! # `nat.pow`
Results on the power operation on natural numbers.
-/
namespace nat
/-! ### `pow` -/
-- This is redundant with `pow_le_pow_of_le_left'`,
-- We leave a version in the `nat` namespace as well.
-- (The global `pow_le_pow_of_le_left` needs an extra hypothesis `0 ≀ x`.)
protected theorem pow_le_pow_of_le_left {x y : β„•} (H : x ≀ y) : βˆ€ i : β„•, x^i ≀ y^i :=
pow_le_pow_of_le_left' H
theorem pow_le_pow_of_le_right {x : β„•} (H : 0 < x) {i j : β„•} (h : i ≀ j) : x ^ i ≀ x ^ j :=
pow_le_pow' H h
theorem pow_lt_pow_of_lt_left {x y : β„•} (H : x < y) {i} (h : 0 < i) : x^i < y^i :=
pow_lt_pow_of_lt_left H (zero_le _) h
theorem pow_lt_pow_of_lt_right {x : β„•} (H : 1 < x) {i j : β„•} (h : i < j) : x^i < x^j :=
pow_lt_pow H h
lemma pow_lt_pow_succ {p : β„•} (h : 1 < p) (n : β„•) : p^n < p^(n+1) :=
pow_lt_pow_of_lt_right h n.lt_succ_self
lemma lt_pow_self {p : β„•} (h : 1 < p) : βˆ€ n : β„•, n < p ^ n
| 0 := by simp [zero_lt_one]
| (n+1) := calc
n + 1 < p^n + 1 : nat.add_lt_add_right (lt_pow_self _) _
... ≀ p ^ (n+1) : pow_lt_pow_succ h _
lemma lt_two_pow (n : β„•) : n < 2^n :=
lt_pow_self dec_trivial n
lemma one_le_pow (n m : β„•) (h : 0 < m) : 1 ≀ m^n :=
by { rw ←one_pow n, exact nat.pow_le_pow_of_le_left h n }
lemma one_le_pow' (n m : β„•) : 1 ≀ (m+1)^n := one_le_pow n (m+1) (succ_pos m)
lemma one_le_two_pow (n : β„•) : 1 ≀ 2^n := one_le_pow n 2 dec_trivial
lemma one_lt_pow (n m : β„•) (hβ‚€ : 0 < n) (h₁ : 1 < m) : 1 < m^n :=
by { rw ←one_pow n, exact pow_lt_pow_of_lt_left h₁ hβ‚€ }
lemma one_lt_pow' (n m : β„•) : 1 < (m+2)^(n+1) :=
one_lt_pow (n+1) (m+2) (succ_pos n) (nat.lt_of_sub_eq_succ rfl)
@[simp] lemma one_lt_pow_iff {k n : β„•} (h : 0 β‰  k) : 1 < n ^ k ↔ 1 < n :=
begin
cases n,
{ cases k; simp [zero_pow_eq] },
cases n,
{ rw one_pow },
refine ⟨λ _, one_lt_succ_succ n, λ _, _⟩,
induction k with k hk,
{ exact absurd rfl h },
cases k,
{ simp },
exact one_lt_mul (one_lt_succ_succ _).le (hk (succ_ne_zero k).symm),
end
lemma one_lt_two_pow (n : β„•) (hβ‚€ : 0 < n) : 1 < 2^n := one_lt_pow n 2 hβ‚€ dec_trivial
lemma one_lt_two_pow' (n : β„•) : 1 < 2^(n+1) := one_lt_pow (n+1) 2 (succ_pos n) dec_trivial
lemma pow_right_strict_mono {x : β„•} (k : 2 ≀ x) : strict_mono (Ξ» (n : β„•), x^n) :=
Ξ» _ _, pow_lt_pow_of_lt_right k
lemma pow_le_iff_le_right {x m n : β„•} (k : 2 ≀ x) : x^m ≀ x^n ↔ m ≀ n :=
strict_mono.le_iff_le (pow_right_strict_mono k)
lemma pow_lt_iff_lt_right {x m n : β„•} (k : 2 ≀ x) : x^m < x^n ↔ m < n :=
strict_mono.lt_iff_lt (pow_right_strict_mono k)
lemma pow_right_injective {x : β„•} (k : 2 ≀ x) : function.injective (Ξ» (n : β„•), x^n) :=
strict_mono.injective (pow_right_strict_mono k)
lemma pow_left_strict_mono {m : β„•} (k : 1 ≀ m) : strict_mono (Ξ» (x : β„•), x^m) :=
Ξ» _ _ h, pow_lt_pow_of_lt_left h k
lemma mul_lt_mul_pow_succ {n a q : β„•} (a0 : 0 < a) (q1 : 1 < q) :
n * q < a * q ^ (n + 1) :=
begin
rw [pow_succ', ← mul_assoc, mul_lt_mul_right (zero_lt_one.trans q1)],
exact lt_mul_of_one_le_of_lt (nat.succ_le_iff.mpr a0) (nat.lt_pow_self q1 n),
end
end nat
lemma strict_mono.nat_pow {n : β„•} (hn : 1 ≀ n) {f : β„• β†’ β„•} (hf : strict_mono f) :
strict_mono (Ξ» m, (f m) ^ n) :=
(nat.pow_left_strict_mono hn).comp hf
namespace nat
lemma pow_le_iff_le_left {m x y : β„•} (k : 1 ≀ m) : x^m ≀ y^m ↔ x ≀ y :=
strict_mono.le_iff_le (pow_left_strict_mono k)
lemma pow_lt_iff_lt_left {m x y : β„•} (k : 1 ≀ m) : x^m < y^m ↔ x < y :=
strict_mono.lt_iff_lt (pow_left_strict_mono k)
lemma pow_left_injective {m : β„•} (k : 1 ≀ m) : function.injective (Ξ» (x : β„•), x^m) :=
strict_mono.injective (pow_left_strict_mono k)
theorem sq_sub_sq (a b : β„•) : a ^ 2 - b ^ 2 = (a + b) * (a - b) :=
by { rw [sq, sq], exact nat.mul_self_sub_mul_self_eq a b }
alias sq_sub_sq ← pow_two_sub_pow_two
/-! ### `pow` and `mod` / `dvd` -/
theorem pow_mod (a b n : β„•) : a ^ b % n = (a % n) ^ b % n :=
begin
induction b with b ih,
refl, simp [pow_succ, nat.mul_mod, ih],
end
theorem mod_pow_succ {b : β„•} (w m : β„•) :
m % (b^succ w) = b * (m/b % b^w) + m % b :=
begin
by_cases b_h : b = 0,
{ simp [b_h, pow_succ], },
have b_pos := nat.pos_of_ne_zero b_h,
apply nat.strong_induction_on m,
clear m,
intros p IH,
cases lt_or_ge p (b^succ w) with h₁ h₁,
-- base case: p < b^succ w
{ have hβ‚‚ : p / b < b^w,
{ rw [div_lt_iff_lt_mul b_pos],
simpa [pow_succ'] using h₁ },
rw [mod_eq_of_lt h₁, mod_eq_of_lt hβ‚‚],
simp [div_add_mod] },
-- step: p β‰₯ b^succ w
{ -- Generate condition for induction hypothesis
have hβ‚‚ : p - b^succ w < p,
{ exact tsub_lt_self ((pow_pos b_pos _).trans_le h₁) (pow_pos b_pos _) },
-- Apply induction
rw [mod_eq_sub_mod h₁, IH _ hβ‚‚],
-- Normalize goal and h1
simp only [pow_succ],
simp only [ge, pow_succ] at h₁,
-- Pull subtraction outside mod and div
rw [sub_mul_mod _ _ _ h₁, sub_mul_div _ _ _ h₁],
-- Cancel subtraction inside mod b^w
have p_b_ge : b^w ≀ p / b,
{ rw [le_div_iff_mul_le b_pos, mul_comm],
exact h₁ },
rw [eq.symm (mod_eq_sub_mod p_b_ge)] }
end
lemma pow_dvd_pow_iff_pow_le_pow {k l : β„•} : Ξ  {x : β„•} (w : 0 < x), x^k ∣ x^l ↔ x^k ≀ x^l
| (x+1) w :=
begin
split,
{ intro a, exact le_of_dvd (pow_pos (succ_pos x) l) a, },
{ intro a, cases x with x,
{ simp only [one_pow], },
{ have le := (pow_le_iff_le_right (nat.le_add_left _ _)).mp a,
use (x+2)^(l-k),
rw [←pow_add, add_comm k, tsub_add_cancel_of_le le], } }
end
/-- If `1 < x`, then `x^k` divides `x^l` if and only if `k` is at most `l`. -/
lemma pow_dvd_pow_iff_le_right {x k l : β„•} (w : 1 < x) : x^k ∣ x^l ↔ k ≀ l :=
by rw [pow_dvd_pow_iff_pow_le_pow (lt_of_succ_lt w), pow_le_iff_le_right w]
lemma pow_dvd_pow_iff_le_right' {b k l : β„•} : (b+2)^k ∣ (b+2)^l ↔ k ≀ l :=
pow_dvd_pow_iff_le_right (nat.lt_of_sub_eq_succ rfl)
lemma not_pos_pow_dvd : βˆ€ {p k : β„•} (hp : 1 < p) (hk : 1 < k), Β¬ p^k ∣ p
| (succ p) (succ k) hp hk h :=
have succ p * (succ p)^k ∣ succ p * 1, by simpa [pow_succ] using h,
have (succ p) ^ k ∣ 1, from dvd_of_mul_dvd_mul_left (succ_pos _) this,
have he : (succ p) ^ k = 1, from eq_one_of_dvd_one this,
have k < (succ p) ^ k, from lt_pow_self hp k,
have k < 1, by rwa [he] at this,
have k = 0, from nat.eq_zero_of_le_zero $ le_of_lt_succ this,
have 1 < 1, by rwa [this] at hk,
absurd this dec_trivial
lemma pow_dvd_of_le_of_pow_dvd {p m n k : β„•} (hmn : m ≀ n) (hdiv : p ^ n ∣ k) : p ^ m ∣ k :=
(pow_dvd_pow _ hmn).trans hdiv
lemma dvd_of_pow_dvd {p k m : β„•} (hk : 1 ≀ k) (hpk : p^k ∣ m) : p ∣ m :=
by rw ←pow_one p; exact pow_dvd_of_le_of_pow_dvd hk hpk
lemma pow_div {x m n : β„•} (h : n ≀ m) (hx : 0 < x) : x ^ m / x ^ n = x ^ (m - n) :=
by rw [nat.div_eq_iff_eq_mul_left (pow_pos hx n) (pow_dvd_pow _ h), pow_sub_mul_pow _ h]
lemma lt_of_pow_dvd_right {p i n : β„•} (hn : n β‰  0) (hp : 2 ≀ p) (h : p ^ i ∣ n) : i < n :=
begin
rw ←pow_lt_iff_lt_right hp,
exact lt_of_le_of_lt (le_of_dvd hn.bot_lt h) (lt_pow_self (succ_le_iff.mp hp) n),
end
/-! ### `shiftl` and `shiftr` -/
lemma shiftl_eq_mul_pow (m) : βˆ€ n, shiftl m n = m * 2 ^ n
| 0 := (nat.mul_one _).symm
| (k+1) := show bit0 (shiftl m k) = m * (2 * 2 ^ k),
by rw [bit0_val, shiftl_eq_mul_pow, mul_left_comm, mul_comm 2]
lemma shiftl'_tt_eq_mul_pow (m) : βˆ€ n, shiftl' tt m n + 1 = (m + 1) * 2 ^ n
| 0 := by simp [shiftl, shiftl', pow_zero, nat.one_mul]
| (k+1) :=
begin
change bit1 (shiftl' tt m k) + 1 = (m + 1) * (2 * 2 ^ k),
rw bit1_val,
change 2 * (shiftl' tt m k + 1) = _,
rw [shiftl'_tt_eq_mul_pow, mul_left_comm, mul_comm 2],
end
lemma one_shiftl (n) : shiftl 1 n = 2 ^ n :=
(shiftl_eq_mul_pow _ _).trans (nat.one_mul _)
@[simp] lemma zero_shiftl (n) : shiftl 0 n = 0 :=
(shiftl_eq_mul_pow _ _).trans (nat.zero_mul _)
lemma shiftr_eq_div_pow (m) : βˆ€ n, shiftr m n = m / 2 ^ n
| 0 := (nat.div_one _).symm
| (k+1) := (congr_arg div2 (shiftr_eq_div_pow k)).trans $
by rw [div2_val, nat.div_div_eq_div_mul, mul_comm]; refl
@[simp] lemma zero_shiftr (n) : shiftr 0 n = 0 :=
(shiftr_eq_div_pow _ _).trans (nat.zero_div _)
theorem shiftl'_ne_zero_left (b) {m} (h : m β‰  0) (n) : shiftl' b m n β‰  0 :=
by induction n; simp [shiftl', bit_ne_zero, *]
theorem shiftl'_tt_ne_zero (m) : βˆ€ {n} (h : n β‰  0), shiftl' tt m n β‰  0
| 0 h := absurd rfl h
| (succ n) _ := nat.bit1_ne_zero _
/-! ### `size` -/
@[simp] theorem size_zero : size 0 = 0 := by simp [size]
@[simp] theorem size_bit {b n} (h : bit b n β‰  0) : size (bit b n) = succ (size n) :=
begin
rw size,
conv { to_lhs, rw [binary_rec], simp [h] },
rw div2_bit,
end
@[simp] theorem size_bit0 {n} (h : n β‰  0) : size (bit0 n) = succ (size n) :=
@size_bit ff n (nat.bit0_ne_zero h)
@[simp] theorem size_bit1 (n) : size (bit1 n) = succ (size n) :=
@size_bit tt n (nat.bit1_ne_zero n)
@[simp] theorem size_one : size 1 = 1 :=
show size (bit1 0) = 1, by rw [size_bit1, size_zero]
@[simp] theorem size_shiftl' {b m n} (h : shiftl' b m n β‰  0) :
size (shiftl' b m n) = size m + n :=
begin
induction n with n IH; simp [shiftl'] at h ⊒,
rw [size_bit h, nat.add_succ],
by_cases s0 : shiftl' b m n = 0; [skip, rw [IH s0]],
rw s0 at h ⊒,
cases b, {exact absurd rfl h},
have : shiftl' tt m n + 1 = 1 := congr_arg (+1) s0,
rw [shiftl'_tt_eq_mul_pow] at this,
obtain rfl := succ.inj (eq_one_of_dvd_one ⟨_, this.symm⟩),
rw one_mul at this,
obtain rfl : n = 0 := nat.eq_zero_of_le_zero (le_of_not_gt $ Ξ» hn,
ne_of_gt (pow_lt_pow_of_lt_right dec_trivial hn) this),
refl
end
@[simp] theorem size_shiftl {m} (h : m β‰  0) (n) :
size (shiftl m n) = size m + n :=
size_shiftl' (shiftl'_ne_zero_left _ h _)
theorem lt_size_self (n : β„•) : n < 2^size n :=
begin
rw [← one_shiftl],
have : βˆ€ {n}, n = 0 β†’ n < shiftl 1 (size n), { simp },
apply binary_rec _ _ n, {apply this rfl},
intros b n IH,
by_cases bit b n = 0, {apply this h},
rw [size_bit h, shiftl_succ],
exact bit_lt_bit0 _ IH
end
theorem size_le {m n : β„•} : size m ≀ n ↔ m < 2^n :=
⟨λ h, lt_of_lt_of_le (lt_size_self _) (pow_le_pow_of_le_right dec_trivial h),
begin
rw [← one_shiftl], revert n,
apply binary_rec _ _ m,
{ intros n h, simp },
{ intros b m IH n h,
by_cases e : bit b m = 0, { simp [e] },
rw [size_bit e],
cases n with n,
{ exact e.elim (nat.eq_zero_of_le_zero (le_of_lt_succ h)) },
{ apply succ_le_succ (IH _),
apply lt_imp_lt_of_le_imp_le (Ξ» h', bit0_le_bit _ h') h } }
end⟩
theorem lt_size {m n : β„•} : m < size n ↔ 2^m ≀ n :=
by rw [← not_lt, decidable.iff_not_comm, not_lt, size_le]
theorem size_pos {n : β„•} : 0 < size n ↔ 0 < n :=
by rw lt_size; refl
theorem size_eq_zero {n : β„•} : size n = 0 ↔ n = 0 :=
by have := @size_pos n; simp [pos_iff_ne_zero] at this;
exact decidable.not_iff_not.1 this
theorem size_pow {n : β„•} : size (2^n) = n+1 :=
le_antisymm
(size_le.2 $ pow_lt_pow_of_lt_right dec_trivial (lt_succ_self _))
(lt_size.2 $ le_rfl)
theorem size_le_size {m n : β„•} (h : m ≀ n) : size m ≀ size n :=
size_le.2 $ lt_of_le_of_lt h (lt_size_self _)
end nat